Causal Factors Related to Medication Errors in Community Pharmacy Department in Phra Nakhon Si Ayutthaya Province - ฤกษ์ชัยศรี ศริลรัชน์; สีตกะลิน พาณี; กีระพงษ์ พรทิพย์ (Journal of Preventive Medicine Association of Thailand, 2018)
This documentary research aimed to study the nature of medication errors and identify causal factors that were related to medication errors, all in the pre-dispensing process for outpatients at the Community Pharmacy Department in Phra Nakhon Si Ayutthaya province. The study was conducted on a sample of 500 outpatient prescriptions given from October 1, 2015 to December 31, 2015 except weekends and public holidays, excluding any prescriptions that did not contain any drug items. The statistics used for data analysis were frequency, percentage, and chi-square test. The results showed that the nature of medication errors, of all 500 outpatient prescriptions, 117 (23.4%) had medication errors in the pre-dispensing process, and the causal factors significantly related to medication errors in the pre-disposing process for outpatients were drug-name similarity, same-drug with strength differences, close proximity of drugs with similar names, close proximity of drugs with similar features, and close proximity of same drugs with different strengths, and number of drugs in one prescription correlated to medication errors with statistical significance at (P<0.05).